Hubungan Pengetahuan Ibu Hamil Tentang Perubahan Psikologi Trimester I dengan Sikap Ibu Hamil dalam Menghadapi Masa Kehamilan di Puskesmas Medan Amplas Tahun 2022 - Rolly Lenci Natalia; Deby Cyntia Yun; Marliani Marliani; Imarina Tarigan (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2022)
Background: Pregnancy is something that naturally happens to productive women. During pregnancy, changes occur in the mother, both physical and psychological. In general, the physical changes during pregnancy are, no menstruation, enlargement of the breasts, changes in the shape of the uterus, changes in the working system of the body's organs, enlargement of the stomach, weight gain, weakening of the relaxation of the muscles of the digestive tract, sensitivity to the senses, and the feet and hands begin to enlarge. The psychological changes in mothers in the first trimester are estimated to be 80%, resulting in feelings of disappointment, rejection, anxiety and sadness. In the second trimester, the mother's psychological life appears calmer and begins to adapt, and in the third trimester, changes in the mother's psychology seem more complex and increase again compared to the previous trimester, and this is none other than because the condition of the pregnancy is getting bigger. Psychological impacts on pregnant women include being sensitive, tending to be lazy, asking for more attention, easily jealous, and anxiety. Pregnant women will be more open to themselves and like to share their experiences with other people. Pregnant women will reflect on all their dreams, dreams, fantasies about objects, events or abstract concepts, such as death, life, success and happiness during pregnancy.Objective: Knowing how the knowledge of pregnant women about psychological changes in the first trimester is related to the attitude of pregnant women in facing pregnancy at the Medan Amplas Community Health Center, Medan City in 2022. Method There is a relationship between the knowledge of pregnant women about psychological changes in the first trimester and the attitude of pregnant women in facing pregnancy at the Medan Amplas Community Health Center, Medan City in 2022. Advice is given for research and for research sites and for educational institutions regarding perennial wound care.